The impact of hillslope groundwater dynamics and landscape functioning in event-flow generation: a field study in the Rietholzbach catchment, Switzerland - von Freyberg, Jana; Rao, P. Suresh C.; Radny, Dirk; Schirmer, Mario (Hydrogeology journal, 2015)
A reliable prediction of hydrograph responses in mountainous headwater catchments requires a mechanistic understanding of the coupled hydro-climatic processes in these regions. This study shows that only a small fraction of the total area in a pre-Alpine headwater catchment actively regulates streamflow responses to hydro-climatic forcing, which facilitates the application of a parsimonious framework for hydrograph time-series prediction. Based on landscape analysis and hydrometric data from the Upper Rietholzbach catchment (URHB, 0.94 km 2 , northeast Switzerland), a conceptual model was established. Here, the rainfall-event-driven contribution of surface runoff and subsurface flow (event flow) accounts for around 50 % of total river discharge. The event-flow hydrograph is generated from approximately 25 % of the entire area consisting of riparian zones (8 %) and adjacent hillslopes (17 %), each with characteristic streamflow-generating mechanisms. Baseflow generation is attributed to deep groundwater discharge from a fractured-rock aquifer covering ∼75 % of the catchment area. A minimalistic model, that represents event flow as depletion of two parallel linear reservoirs, verified the conceptual model of the URHB with adequate hydrograph simulations  ( R 2 = 0.67, Nash-Sutcliffe efficiency (NSE) = 0.64). Hereby, the expansion of the event-flow contributing areas was found to be particularly significant during long and high-intensity rainfall events. These findings provide a generalized approach for the large-scale characterization of groundwater recharge and hydrological behavior of mountainous catchments with similar landscape properties.